Economic Sanctions and Public Opinion: Survey Experiments From Russia. (June 2019) - Frye, Timothy
Do economic sanctions turn the public against the target government or cause it to rally around the flag? How do sanctions affect attitudes toward the sanctioner? How does bad economic performance under sanctions shape support for the target government? Despite their importance, these questions have rarely been explored with survey data. Results from two surveys in Russia find that exposure to information about economic sanctions does not generate a rally around the flag, leads some groups to withdraw support from the target government, and reduces support for the sanctioner. Respondents also react more strongly to the reasons why sanctions were put in place—the annexation of Crimea—than to the sanctions themselves. These results suggest the need to reevaluate theories of the impact of economic sanctions and blame-shifting under autocracy.